Comparative Evaluation of Microleakage Around Pre-Endodontic Buildup with Composite, Light Cured Glass Ionomer Cement, and Glass Ionomer Cement: An In-Vitro Study - Avneel Neema; Santosh K. Singh; Khushboo Magwa; Juhi Deopujari; Jasleen Suri; Shriya Mitna (Journal of Pharmacy and Bioallied Sciences)
Objective: To compare the microleakage of three different restorative materials used in pre-endodontic buildup: Bulk Filled Composite, Light Cured Glass Ionomer Cement (GIC), and Conventional GIC. Methods: This in-vitro study involved 36 extracted human molars divided into three groups, each restored with one of the aforementioned materials. Standardized class V cavities were prepared and restored according to manufacturer instructions. The teeth underwent thermocycling and were immersed in methylene blue dye to assess microleakage. Results: Bulk Filled Composite exhibited the least microleakage (Mean = 3.9047, SD = 0.79519), followed by Light Cure GIC (Mean = 4.9628, SD = 1.87938) and GIC (Mean = 5.6244, SD = 1.55793). Statistical analysis using ANOVA revealed significant differences in microleakage among the groups (F-statistic = 4.109, P = 0.025). Conclusion: Bulk Filled Composite demonstrated superior performance in reducing microleakage compared to both forms of GIC. This suggests that Bulk Filled Composite is more effective for pre-endodontic restorations where minimizing microleakage is critical for successful endodontic therapy.